Characterization of the morphometry, germination process, phytochemicals, and antioxidant capacity of seeds of three species of the genus Cylindropuntia (Cactacea) of Chihuahua state - Reyes-Corral, Valeria Itzel; Gonzalez Fernandez, Raquel; Quiñonez Martínez, Miroslava; Rodrigo Garcia, Joaquin; Valero Galván, José; Garza-Vallejo, Gerardo Ivan (2022)
Abstract. Cylindropuntia is a genus of cylindrical cacti found in northern Mexico. This study aimed to describe the fruit and seed morphometry, characterize the germination process, as well as determine the seed phytochemicals in three species of the genus Cylindropuntia from the state of Chihuahua in México: C. imbricata, C. spinosior, and C. leptocaulis. To measure the morphometric parameters, 20 fruits and 20 seeds from each fruit were used for each specie. For the characterization of the germination process, two scarification treatments were applied, and the germination was allowed for 42 days. Different parameters of the germination process were calculated as the germination percentage, mean germination time, germination speed, and mean germination speed. The concentration of reducing sugars, total phenols, tannins, flavonoids, antioxidant activity (DPPH and FRAP), and protein content were determined from seeds under basal conditions. Results revealed significant differences (p ≤ 0.05) for morphometric parameters in the fruit and seed of the three species examined, showing C. imbricata the highest values in both tissues, followed by those obtained for C. spinosior and C. leptocaulis, respectively. The germination percentage was higher in C. leptocaulis (13.3%), although achieved in a longer mean germination time (27.7 days), facing C. spinosior that presented the lowest values for the germination percentage (3.3%), mean germination time (4.6 days), and germination speed index (0.024 days). Seeds from C. leptocaulis showed the highest values for reducing sugar content (31.82 mg glucose·g −1 of dry weight) and the antioxidant activity determined by DPPH (26.37 mg CE·g−1of dry weight), whereas C. spinosior seeds showed the highest ones for the total phenols content (3.08 mg GAE·g−1 of dry weight) and the antioxidant activity determined by FRAP (11.7 mmol TE·g −1 dry weight). Besides, C. imbricata showed the highest value in the protein content (5.6 mg protein·g −1 ). This study provides the first data on seed phytochemicals and information on the germination process of these three species of Cylindropuntia, showing differences among them in the diverse parameters measured.